Global smooth solutions for the inviscid SQG equation - Castro, Angel, 1982-; Córdoba Gazolaz, Diego, 1971-; Gomez-Serrano, Javier, 1985- (Memoirs of the American Mathematical Society, 2020)
"In this memoir, we show the existence of the first non trivial family of classical global solutions of the inviscid surface quasi-geostrophic equation"--